PERADABAN ISLAM PADA MASA NABI MUHAMMAD SAW PERIODE MEKAH - Rumondang, Tetti; Sormin, Darliana; Uswatun, Putri; Aminah, siti (Universitas Muhammadiyah Tapanuli Selatan, 2023)
This study discusses Islamic civilization during the time of the Prophet Muhammad SAW Mecca Period. The purpose of this study was to find out what strategy the Prophet used in spreading Islam in Mecca. This type of research is library research. This research makes Library materials as its main data source. The results of the research obtained are, the early Islamic history passed by the Holy Prophetsa was very difficult because it had to be faced by the Quraysh tribe who controlled the city of Mecca. The followers of the Holy Prophetsa were relatively few and the main focus of the Holy Prophetsa in his early da'wah was to introduce the teachings of Tawhid. The focus of the Prophet's da'wah was to teach Islamic sharia and Islamic law. The implications of the discussion of Islamic history in the period of Mecca and Medina, as follows: a) Understanding Islam as a rahmatan lil alamin (mercy for all nature); and b) Understand Islam as a religion that loves tolerance, as in the event of Fathul Makkah the Holy Prophetsa still valued idolaters. And what strategy the Prophet used in spreading Islam in Mecca was by preaching secretly and openly.